Bankruptcy law, capital allocation, and aggregate effects: a dynamic heterogeneous agent model with incomplete markets - Tao Zha (Federal Reserve Bank of Atlanta, 1995)
Under the assumption that asset markets are incomplete, this paper introduces bankruptcy in an intertemporal heterogeneous agent model with capital accumulation and heterogeneous agents. It explores the role of regulatory intervention and argues that intervention in the form of a level of bankruptcy exemption can enhance not only social welfare but also distributive equity. The bankruptcy law is carefully specified in the model. The model generates distributional changes in consumption, capital, and bankruptcy risk in response to an adjustment in the exemption level and accentuates the effects of these redistributions on aggregate variables.
Keywords: 330; Bankruptcy; Financial markets